The impact of the risks of foreign currency positions in the audit procedures : Applied research (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to know the extent of the impact of the risks of foreign exchange centers represented in the risks of commitment, exchange rate changes and liquidity risks in audit procedures, and accordingly the research will provide an applied framework of knowledge that shows the relationship between the variables addressed, and the importance of the research lies in the light of its presentation of intellectual, cognitive and applied contributions On the risks of foreign exchange centers and audit procedures, the research community is represented in the banking sector. The sample included nine private commercial banks listed in the Iraqi Stock Exchange. The research relied on a time series consisting of four years that extended from 2017 to 2020. The research problem was in Audit procedures to verify and identify risks related to foreign currency positions within the banking activity. The research relied on financial indicators to measure the risks of foreign currency centers, and on the development of proposed audit procedures for auditing foreign currency centers and their application in the banks of the research sample, reinforced by statistical methods and programs represented by the (SPSS) program to test the research hypotheses, and the most important conclusions that he reached. Auditing foreign currency positions for non-trading purposes from the auditor helps reduce the impact of the risks of these positions (compliance risk, liquidity risk, and exchange rate change risks), as it needs audit procedures carried out by the auditor to discover its dangers, and the most important recommendations reached . Auditors should pay attention to auditing foreign currency positions for non-trading purposes because of their impact on banks, as it is possible to be guided by the procedures proposed by the researcher to audit foreign currency positions, as well as the proposed indicators to measure their risks, to know and identify the risks related to them well.